Digital Dictionary Vs Non-Digital Dictionary; The Needs, Challenges, and Effects in English Language Learning - Saini, Fadhlan; Bale, Ghifar (Institut Agama Islam Negeri (IAIN) Manado, 2025)
This research explores the needs, challenges, and effects of using both digital and non-digital dictionaries in English language learning. The research design employed a qualitative study with data analysis conducted using Lisabella (2013)’s model. The participants involved 15 students as informants from several different universities in North Sulawesi. These participants were the sample who registered in the English Education Department / Study Program and English Literature Program. The research instruments used were observation and semi-structured interviews to collect data on students’ perceptions related to the issue. Data analysis was carried out by identifying students’ responses. Findings reveal that while both formats support vocabulary development and language comprehension, digital dictionaries are preferred for their speed, convenience, and rich features such as audio pronunciation and contextual examples. However, challenges such as internet dependency, distracting advertisements, and potential overreliance were identified. These limitations underscore the need for improved digital tool design and greater student awareness. The study highlights the importance of fostering digital literacy and strategic dictionary use to enhance long-term vocabulary retention, communication skills, and overall language proficiency.Keywords: Digital Dictionaries, Non-Digital Dictionaries, English language learning